In Silico Clinical Trials as a Strategic tool in Modern Drug Development - Kathale Ankita A; Khaire Rahul D; KoradePayal B; Sankhe Lochani D; Bhandare Tejashwini S; Ghuge Samiksha K (Asian Journal of Pharmaceutical Research and Development, 2025)
Medicine discovery and development are resource- ferocious processes, frequently hindered by high failure rates during clinical trials. In silico clinical trials( ISCTs) — computer- grounded simulations of mortal trials have surfaced as a transformative tool in ultramodern medicine development. By using computational models, real case data, and artificial intelligence, ISCTs enable the varification of medicine efficacy , safety, and optimal lozenge without risking mortal subjects. These simulations can induce virtual case populations, streamline trial designs, reduce costs, and ameliorate time- to- request effectiveness. ISCTs are particularly salutary in studying rare conditions, pediatric populations, and substantiated drug approaches. While promising, challenges similar as model confirmation, data quality, nonsupervisory acceptance, and ethical enterprises remain. With advancing technologies like AI, digital halves, and amount computing, ISCTs are poised to revise pharmaceutical exploration by offering safer, briskly, and further cost-effective pathways to medicine development..